Workshop Pemanfaatan Lingkungan Belajar di Sekitar Sekolah dalam Pembelajaran Matematika bagi Guru Sekolah Dasar di Gugus IV Kecamatan Siak Hulu, Kampar - Zetra Hainul Putra; Intan Kartika Sari; Gustimal Witri; Syahrilfuddin Syahrilfuddin; Neni Hermita; Mahmud Alpusari; Eddy Noviana; Munjiatun Munjiatun; Muhammad Ramadhan; Yesi Martha Afrillia; Sabrina Eka Putri (Universitas Mathla'ul Anwar Banten, 2020)
WORKSHOP OF UTILIZATION OF LEARNING ENVIRONTMENT AROUND SCHOOLS IN MATHEMATICS LEARNING FOR ELEMENTARY SCHOOL TEACHERS IN SIAK HULU, KAMPAR. The workshop on the utilization of learning environment was motivated by the lack of teachers' mathematical and didactical knowledge. Teachers tend to explain techniques or procedures for solving mathematical problems without explaining the real context or situation of the problem, and this is contrary to the theories of mathematical learning that develop, such as the cognitive development theory, the realistic mathematics education, and the didactic situation theory. In addressing this problem, the team held a week workshop consisting of the lectures, observation, lesson plans, and implementation of learning by the teachers participating in the workshop, and reflection and evaluation of workshop activities. The data collection instrument consists of a questionnaire measuring the attitudes and beliefs of teachers towards mathematics, students learning mathematics, and mathematics learning based on real environments, photos, video recordings, and documents produced by the participants. The results of the implementation of this workshop show an increase in teachers' beliefs and attitudes towards students learning and mathematics learning based on real-life situations. Some participants were able to present the potential of the school environment as a source of learning mathematics, compile lesson plans, and carry out environment-based mathematics learning. The recommendation from this activity is that in the future it is necessary to have a service program that focuses on strengthening the teachers' mathematics content knowledge and making mathematics learning media and/or teaching aids.